First report of Livoneca guianensis (Isopoda: Cymothoidae) in Leporinus fasciatus (Pisces: Anostomidae) in Brazil - Marcos Sidney Brito Oliveira; Marcos Tavares-Dias (Revista Brasileira de Parasitologia Veterinária, 2020)
Abstract This study aimed to report the first record of the occurrence of the parasite Livoneca guianensis in Leporinus fasciatus in Brazil. In September 2019, during surveys of the parasites in 12 specimens of L. fasciatus from the lower Jari River basin, in Amapá State, Brazil, one specimen of L. guianensis was found in the tongue of one host. The prevalence of L. guianensis was 8.3%, and it was observed that this parasite has a geographic distribution restricted to South America, parasitizing fish species from Guyana and Brazil. This study contributed to the first report on the occurrence of L. guianensis for L. fasciatus in Brazil. In addition, increased the knowledge on the geographic distribution of this parasite with morphometric data, which are scarce for this Cymothoidae.